Web-Based Expert System for Eye Disease Diagnosis Using Certainty Factor Method: Sistem Pakar Berbasis Web untuk Diagnosa Penyakit Mata Menggunakan Metode Certainty Factor - Adimas Priyambadha; Ade Eviyanti (Academia Open, 2023)
General background Eye diseases are a significant health issue and often go undiagnosed accurately. Specific background With advancements in technology, web-based expert systems offer solutions for more efficient and accurate diagnosis. Knowledge gap However, there are still limitations in the application of systematic diagnostic methods in the context of eye diseases. Aims This research aims to develop an expert system that can diagnose eye diseases using the Certainty Factor method. Results The designed system successfully identified the symptoms of eye diseases with a high accuracy percentage, providing relevant diagnosis results based on user input. Novelty This study introduces the use of the Certainty Factor method in an expert system specifically for eye diseases, which has not been widely applied before. Implications These findings are expected to help raise public awareness about eye health and encourage users to consult with specialists after receiving results from the expert system. Thus, this system not only functions as a diagnostic tool but also serves as an educational medium for users. Highlights: Development of an expert system for diagnosing eye diseases using the Certainty Factor method. The system demonstrates high accuracy in identifying symptoms based on user input. Provides an educational platform to raise awareness about eye health among users. Keywords: Expert system, Eye Disease, Certainty Factor, Web-Based Application, Diagnosis